Bottom aquaculture can improve the basic trophic pathways and enhance the secondary production: Implications from benthic food web analysis. (April 2022) - Wang, Qi; Fu, Shanshan; Mu, Fanghong; Zhang, Zhinan; Liu, Xiaoshou
Abstract: To evaluate the impact of bottom aquaculture on benthic ecosystems, characteristics of benthic food web were studied using stable isotope techniques during four seasons in a Manila clam ( Ruditapes philippinarum ) bottom aquaculture area in a semi-enclosed bay, China. Results showed that although nitrogen stable isotope values of food sources (particulate organic matter and phytoplankton) had significant seasonal differences, there were no significant seasonal changes for benthic food web structure. Manila clam bottom aquaculture can enhance the secondary productivity and improve the basic trophic pathways by providing bio-deposits. Besides particulate organic matter and phytoplankton, Manila clam could feed on self-generated feces with high nitrogen stable isotope values, and benthic micro- and macroalga with high carbon stable isotope values. Secondary productivity of the stations with a high degree of aquaculture was higher than that of stations with a low degree. Bivalve bottom culture may have a positive impact on benthic ecosystem functioning. Graphical abstract: Unlabelled Image Highlights: Effects of Manila clams on benthic food web were studied by stable isotope technique. Seasonal changes of benthic food web characteristics were not significant. Bottom aquaculture can improve basic trophic pathways of benthic food web. Bottom aquaculture may have a positive impact on ecosystem functioning.